Karakteristik Penderita Skizofrenia Di Rumah Sakit Jiwa PROF. DR. M. ILDREM Tahun 2018-2021 - Agustaria Ginting; Friska Sri Handayani br. Ginting; Dina Sinar Agustina Siregar (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Schizophrenia, a psychotic condition involving social withdrawal, emotional and affective disturbances, and the potential for hallucinations and delusions, serves as the focal point of this research. Symptoms of schizophrenia encompass disruptions in thought processes, emotional effects, volitional disturbances, psychomotor issues, delusions, and hallucinations. The aim of this study is to comprehend the characteristics of schizophrenia patients at Prof. Dr. M. Ildrem Mental Hospital during the period 2018-2021. Employing a descriptive care series approach with a sample size of 100 individuals, the majority of patients are male (54%) with a dominant age range of 17-32 years (66%). Most are unemployed (82%), have completed high school (42%), are unmarried (71%), adhere to Islam (69%), belong to the Batak Toba ethnic group (53%), and commonly exhibit the paranoid subtype of schizophrenia (100%). Recurrence occurs ≥3 times (75%), with hallucinations being a frequently observed symptom (85%). Family involvement in medication control, engaging patients in social activities, and family-oriented events are expected to provide effective support.